Incidencia de Mortalidad Perinatal y Factores Asociados a Mortalidad Neonatal Precoz en el Hospital Daniel Alcides Carrión del Callao Octubre 1994 - Julio 1995 Estudio Exploratorio - Palomino, Eilder (1997)
This study was designed to establish the perinatal mortality rate and the early neonatal mortality associated factors. We analyzed the characteristic of birth registered in the Daniel Alcides A Carrion Hospital in Callao, Lima - Peru, between October 1994 and July 1995. The perinatal mortality rate was 31,8 x 1000 live birth and the early, neonatal mortality rate was 24 x 1000 birth. The associated factors with early neonatal mortality was gestational age less than 37 weeks (RR 21,30 CI 13,61-33,32), low birth weight, lower than 1500 g (RR 123,32 CI 66,44-228,89), and between 1500-2499 g (RR 11,75 CI 7,27-18,97), footling breech presentation (RR 6,42 CI 3,93-10,47), other abnormal presentation (RR 5,88 CI 2,27-15,23), absence of prenatal care (RR 4,56 CI 1,86-11,20), incompleted prenatal care (RR 5,29 CI 1,92-14,60). We found a population attributable risk percent ó'ARP) of 46,9% associated with gestational age less than 37 weeks, 29,1% for low birth weight, lower than 1500 g and 28,7 for the low birth weight between 1500-2500 g. We discuss the relation of these factors with the perinatal mortality generation process and are establish, according to our findings, the possibility of some interventions; such strategies focus oil the population. We conclude that is necessary to get deeper in the investigations related with sonic of these factors and to get uniform both, operational definitions, and epidemiological-statistical analysis methodologies.